Evaluating the changes in sexual function after sterilization in women referring to some selected hospitals in Tehran during 2004 - G Ozgoli; N Sayadian; M Azar; H Alavimajd (JRI, 2005)
Introduction: Female Sterilization is the second most frequent method of contraception (%17.1) after oral contraceptive pills (%18.4) in Iran. Sexual function following the use of this method has not been adequately addressed. The effects of sterilization are different in different individuals. Female sterilization may lead to psychological changes. The positive effects result from the disappearance of the fear of unwanted pregnancies and also side effect of other contraceptive methods and negative effects arise from the sense of preserving the reproductive ability. Retrospective studies usually show an improvement or worsening of sexual functions, but prospective studies show no changes or improvement of female sexual functions. Regarding the impor-tance of sexual function and the high percentage of female sterilization in Iran, the present study was conduc-ted to determine the changes in sexual function of sterilized women referring to some selected hospitals of Tehran in 2004. Materials and Methods: In this study 106 women volunteering for sterilization were selected by stratified sampling and underwent the study before the operation and 3 months after sterilization. All subjects were Ira-nian and monogamous with an anxiety and depression score lower than 2 (by SCL90 test) and had no major stressful events six months before the study. None of them were in postpartum period at the time of surgery. The study included an interview form with two parts: demographic questions (18 items) and questions on sexual function (16 items regarding different phases of sexual desire, sexual arousal, orgasm and resolution) as well as sexual satisfaction items scored by Likert scale. The tool was validated by content validity and its reliability was measured by Cronbach's alpha test. The data were gathered by completion of the forms before and three months after sterilization by one of the researchers (a midwife). Data analysis was done by SPSS (10) software and paired t-test was performed. The significance level was considered 0.05. Results: Findings showed that mean age of women undergoing sterilization was 33.74.2 years. Most subjects were illiterate (%56.6), housewives (%87.7) and their husbands mostly had non-governmental jobs (%51.9). Mean number of gravidity and number of children were 3.71.3 and 3.20.9 respectively. The last contraceptive method used in most of them was OCPs. Their family income was mostly between 110- 165 dollars (%32.1) and most of them (%54.7) had a house of their own. The average percentages of sexual des-ire, sexual arousal, orgasms and sexual functions had no statistically significant differences before and after surgery but resolution phase and sexual satisfaction showed a significant difference (p<0.05) and changed from 68.220.7 to 71.621.4 and from 60.120.5 to 64.321.5 respectively. Conclusion: It seemed that sexual function would not change after 3 months of sterilization, except for the resolution phase and sexual satisfaction which improved postoperatively. There was also a slight increase in other phases over three months of follow-up. As different factors such as culture, religion, individual differ-rences, walks of life and the picture of women portrayed by mass media in the country and factors aside from contraceptive methods, have an exclusive effect on sexual function, these findings are justifiable. However, Long-term studies with longer follow-up periods are suggested for future studies.
Keywords: Female sterilization, Female sexual function index (FSFI), Orgasm, Sexuality, Sexual desire, Tubectomy